Análise de impacto do programa estratégia saúde da família sobre medidas de saúde da população no Brasil – 2019 - Silva, Marcela Belkiss Oliveira da (2022)
The Estratégia Saúde da Família is the most widespread public health policy in Brazil, working to promote health for the population; in which it assumes the health responsibility, considering the dynamics of the people who live in the Brazilian territory. Collective health is a field of national strategic interest; in addition to being a social right, an economic good and a space for capital accumulation. It starts from the idea that the Family Health Strategy is part of a government intervention in the fight against CNCD, understanding that this is a problem that involves the control of obesity and the promotion of healthy eating habits to the Brazilian population. Health, as a strategic field, needs to be measured in terms of its impact on Brazilians, public policy closer to individuals needs to be frequently analyzed so that it is possible to follow its impact trajectory over time, especially in dimensions that are in vogue in discussions of health in several countries around the world. The objective of the study was to understand the impact made by the public health policy, the ESF, on the health of the Brazilian population - considering two dimensions, which are Preventive Health, demonstrated in two variables: the Body Mass Index and the index of eating habits of this population; and the second, CNCDs, which are diabetes, cardiovascular problems and chronic respiratory problems. The data used were obtained from the 2019 National Health Survey – Pesquisa Nacional de Saúde 2019 –, using the Propensity Score Matching method - with the adjustments of 1 nearest neighbor, 5 nearest neighbors and kernel - and Lewbel Method. In this analysis, together, the results did not indicate a significant impact of the program on the health of Brazilian adults in the dimensions of Preventive Health and CNCDs. The difficulties faced by the ESF are directly linked to the proximity of the user, depending on the subjectivities that are not realized within the program guidelines - from its formulation to its application. It is recommended to carry out impact analyzes on a recurring basis to monitor the effectiveness and effectiveness of policies, providing updated data on the population's access and can help improve the quality of life in Brazil.